2020
DOI: 10.1111/iwj.13390
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of multi‐layered silicone foam dressings for prevention of sacral and heel pressure ulcers in high‐risk intensive care unit patients: An economic analysis of a randomised controlled trial

Abstract: Pressure ulcer incidence is high in intensive care units. This causes a serious financial burden to healthcare systems. We evaluated the cost‐effectiveness of multi‐layered silicone foam dressings for prevention of sacral and heel pressure ulcers in addition to standard prevention in high‐risk intensive care units patients. A randomised controlled trial to assess the efficacy of multi‐layered silicone foam dressings to prevent the development of pressure ulcers on heels and sacrum among 422 intensive care unit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…Além das LP serem danosas aos pacientes, o custo do tratamento é alto, portanto, deve-se investir na prevenção (El Genedy et al, 2020;Bezerra et al, 2020).…”
Section: Resultsunclassified
“…Além das LP serem danosas aos pacientes, o custo do tratamento é alto, portanto, deve-se investir na prevenção (El Genedy et al, 2020;Bezerra et al, 2020).…”
Section: Resultsunclassified
“…Studies from other areas of care indicate that regular training has a positive influence and can contribute to improving the quality of care 22 . New innovative processes like the application of local dressings were not common, although recent research results have shown their efficacy 23,24 . The results of the linear regression, although somewhat underpowered, have some interesting results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a separate cost-effectiveness analysis of these data demonstrated that prophylactic dressings are cost-effective especially when applied over the sacrum. 10 The incremental cost per sacral PI prevented was just over €700, or about $750.…”
Section: Commentmentioning
confidence: 99%